2013
DOI: 10.9755/ejfa.v25i4.15494
|View full text |Cite
|
Sign up to set email alerts
|

Protection against lead contamination by strains of lactic acid bacteria from<br>fermented camel milk

Abstract: The effectiveness of the fermented milk product for decreasing the absorption of Lead (Pb) in vivo by testing several combinations of different strains and individual strains of LAB isolated from camel milk and shubat (fermented camel milk) was determined. During 4 weeks 0.5 ppm of Pb was given to cavies in fermented milk product and water. Control group and groups treated only by fermented milk products, also, were observed. Faeces, Blood, Heart, Lungs, Liver, Kidneys, and Spleen were analyzed. The lead conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…These authors showed that the results with Lactobacillus were similar to those obtained using DMSA (meso-2, 3dimercaptosucccinic acid), a known metal chelating agent employed in cases of acute intoxication by metals. Akhmetsadykova et al (2013) demonstrated the effectiveness of fermented camel's milk in decreasing absorption and organ accumulation of Pb in cavies administered for 28 days with fermented milk with a low concentration of Pb (0.5 mg/L).…”
Section: Metals and Metalloidsmentioning
confidence: 95%
“…These authors showed that the results with Lactobacillus were similar to those obtained using DMSA (meso-2, 3dimercaptosucccinic acid), a known metal chelating agent employed in cases of acute intoxication by metals. Akhmetsadykova et al (2013) demonstrated the effectiveness of fermented camel's milk in decreasing absorption and organ accumulation of Pb in cavies administered for 28 days with fermented milk with a low concentration of Pb (0.5 mg/L).…”
Section: Metals and Metalloidsmentioning
confidence: 95%
“…Protection against lead contamination by strains of lactic acid bacteria from fermented camel milk has been reported [9]. One of the most frequently described problems in lead toxicity is saturnism, cancer and anemia.…”
Section: Protection Against Lead Contaminationmentioning
confidence: 99%
“…This supports the finding of the study of cadmium reduction by L. casei. According to Halttunen et al (2007) and Akhmetsadykova et al (2013), there was a considerable reduction in the concentration of lead in solution after biotreatment with L. casei. Halttunen et al (2007) reported up to 97% of lead removal from solution with an initial metal concentration of 100 and 1000 ug/L.…”
Section: Discussionmentioning
confidence: 99%